Epidemiological Manifestations of the Crimean-Congo Hemorrhagic Fever (on the Example of Astrakhan Region) - S. V. Ugleva; V. G. Akimkin (Эпидемиология и вакцинопрофилактика, 2019)
Background. The epidemiological situation in the Astrakhan region indicates the activation of the natural foci of the Crimean-Congo hemorrhagic fever (CCHF), due to a sharp increase in carriers and guardians of the CCHF pathogen, Hyalomma marginatum, on both farm animals and in open biotopes. Natural conditions in combination with human activities (animal husbandry, crop production) and the lack of anti-tick measures create a favorable environment for the population of vectors and, therefore, for the circulation of the CCHF virus.Aim - identification of features of ecological and epidemiological manifestations of the CCHF in the Astrakhan region in 2000-2016.Results. The state of the natural foci of CCHF was monitored, which is endemic and the most severely occurring natural focal disease of arbovirus etiology in the Astrakhan region, preserving the tendency to expand the range. For the analyzed period from 2000 to 2016.151 cases of CCHF were registered in the Astrakhan region, the average long-term incidence rate of the population was 0.88 ± 0.2 per 100 ths of the population. The disease is registered in all districts of the region and the city of Astrakhan, but the largest number is noted in the floodplain-delta regions, where there are favorable conditions for grazing cattle. There is a clear connection between the infection and certain landscapes, where the necessary set of conditions for the circulation of the pathogen is provided.